2004
DOI: 10.1002/bem.20033
|View full text |Cite
|
Sign up to set email alerts
|

Association of residential magnetic fields with contact voltage

Abstract: The US National Electrical Code's (NEC) requirement to ground a home's electrical service to the residential water line results in a voltage between the water line and earth, V W-E. The voltage may result from ground return current that flows into the earth via the water line or from inductive effects from other sources of magnetic fields, such as transmission lines. This voltage can, in turn, serve as a source for Vbath, the voltage between the water fixtures and conductive drain pipes sunk into the earth ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Based on a limited set of measurements in two cities covering a total of 227 residences [Kavet and Zaffanella, 2002;Kavet et al, 2004], the source voltage for a bathing child is commonly no greater than a few hundred millivolts but could be as high as several volts; high levels of neighborhood ground currents, induction from nearby high voltage transmission lines or faulty grounding can be responsible for high levels [Kavet, 2005;Kavet et al, 2006]. For a source voltage of 500 mV, the contact current would range between 25 and 100 mA for subject body-to-bath resistances spanning 0.5-2 kO.…”
Section: Exposurementioning
confidence: 99%
“…Based on a limited set of measurements in two cities covering a total of 227 residences [Kavet and Zaffanella, 2002;Kavet et al, 2004], the source voltage for a bathing child is commonly no greater than a few hundred millivolts but could be as high as several volts; high levels of neighborhood ground currents, induction from nearby high voltage transmission lines or faulty grounding can be responsible for high levels [Kavet, 2005;Kavet et al, 2006]. For a source voltage of 500 mV, the contact current would range between 25 and 100 mA for subject body-to-bath resistances spanning 0.5-2 kO.…”
Section: Exposurementioning
confidence: 99%
“…In previous measurement studies, B avg has been reported as positively associated with V W-E and V bath across residences (Kavet and Zaffanella 2002;Kavet et al 2004). Nonetheless, our understanding of the potential role of V bath in explaining the epidemiologic results would be incomplete without a further understanding of how B avg , V W-E , and V bath are interrelated within residences, which is the issue addressed in the measurements reported in this study.…”
Section: Introductionmentioning
confidence: 51%
“…This voltage, represented in Fig. 1 (left), is also a source of contact current exposure to a bathing child while touching a metal plumbing fixture contiguous with the water line, provided the drain into the earth is conductive (Kavet and Zaffanella 2002;Kavet et al 2004). The voltage across the child is referred to as V bath , which is represented in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…A low prevalence of the highest current, 200 A, does not necessarily lead to a decrement of the association; rather, the balance of weights across all feeder loads plays a role. The diversity of feeder currents together with unbalanced currents across large regional swaths is quite likely a factor largely responsible for the positive relationships between B avg and V W-E that have been measured [Kavet and Zaffanella, 2002;Kavet et al, 2004].…”
Section: Modeling Studymentioning
confidence: 97%